Dinamika Perubahan Sosial Dan Hukum Islam - Azhari, Fathurrahman (AL-TAHRIR, 2016)
Abstract: The Dynamics of Social Change and Islamic Law are related each other in making a change. In the one hand,Â  social changeis caused by the Islamic law, but on the other hand, the change of Islamic law itself is causedby the social changes. The existence of Islamic law, which was broughtÂ  by Rasulullah Saw, had clearly changed the social community at that time;the changes started from jahiliyyah societyera that strongly heldÂ  theirÂ  tradition to the Islamic societyera that held Islamic law.By the same token, Islamic law had also made a change due to social changes. According to juries-prudency of Islamic law(regulations made by fukaha/Islamic cleric) that thechange of the fatwa (advice) was caused by the change of the periode, place, situation (niat) and tradition".Â  By doing the change of law, the Islamic law becomes dynamic, and adaptable and islamic lawswould be up to date in accordance with the current development and the social changes.Ø§Ù„Ù…Ù„Ø®Øµ: Ø§Ù„Ø¯ÙŠÙ†Ø§ Ù…ÙŠÙƒÙŠØ© Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ø£ØÙƒØ§Ù… Ø§Ù„Ø´Ø±Ø¹ÙŠØ© Ù…Ø±ØªØ¨Ø·Ø§Ù† ÙÙŠ Ø¥ÙŠØ¬Ø§Ø¯ Ø§Ù„ØªØºÙŠØ±. Ù…Ù† Ø¬Ù‡Ø© ÙƒØ§Ù† Ø§Ù„ØªØºÙŠØ± Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø¨Ø³Ø¨Ø¨ ÙˆØ¬ÙˆØ¯ Ø§Ù„Ø£ØÙƒØ§Ù… Ø§Ù„Ø´Ø±Ø¹ÙŠØ©. ÙˆÙ…Ù† Ø¬Ù‡Ø© Ø§Ø®Ø±Ù‰ ØªØºÙŠÙ‘Ø± Ø§Ù„ØÙƒÙ… Ø§Ù„Ø´Ø±Ø¹ÙŠ Ø¨Ø³Ø¨Ø¨ Ø§Ù„ØªØºÙŠÙ‘Ø± Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹Ù‰ . ÙˆØ¬ÙˆØ¯ Ø§Ù„Ø´Ø±ÙŠØ¹Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØªÙŠ Ø£ØªÙ‰ Ø¨Ù‡Ø§ Ø§Ù„Ø±Ø³ÙˆÙ„ Ø§Ù„Ù„Ù‡ ØµÙ„Ù‰ Ø§Ù„Ù„Ù‡ Ø¹Ù„ÙŠÙ‡ ÙˆØ³Ù„Ù… ØºÙŠÙ‘Ø±Øª - Ø¨ÙˆØ¶ÙˆØ - Ø§Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Øª ÙÙ‰ Ø°Ù„Ùƒ Ø§Ù„ÙˆÙ‚Øª Ù…Ù† Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø¬Ø§Ù‡Ù„ÙŠØ© Ù…ØªÙ…Ø³ÙƒØ© Ø¨Ø§Ù„Ø¹Ø§Ø¯Ø§Øª Ø¥Ù„Ù‰ Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù…ØªÙ…Ø³ÙƒØ© Ø¨Ø§Ù„Ø´Ø±ÙŠØ¹Ø© Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠØ©. ÙˆÙ„ÙƒÙ† Ø§Ù„Ø£ØÙƒØ§Ù… Ø§Ù„Ø´Ø±Ø¹ÙŠØ© Ø£ÙŠØ¶Ø§ ØªØªØºÙŠØ± Ø¨Ø³Ø¨Ø¨ Ø§Ù„ØªØºÙŠØ± Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø§Ù„Ù…ÙˆØ§ÙÙ‚ Ø¨Ø§Ù„Ù‚Ø§Ø¹Ø¯Ø© Ø§Ù„ÙÙ‚Ù‡ÙŠØ© Ø§Ù„ØªÙŠ ÙˆØ¶Ø¹Ù‡Ø§ Ø§Ù„ÙÙ‚Ù‡Ø§Ø¡ " ØªØºÙŠØ± Ø§Ù„ÙØªÙˆÙ‰ Ø¨ØªØºÙŠØ± Ø§Ù„Ø²Ù…Ø§Ù† ÙˆØ§Ù„Ù…ÙƒØ§Ù† ÙˆØ§Ù„Ø§ØÙˆØ§Ù„ ÙˆØ§Ù„Ø¹Ø§Ø¯Ø© " ÙØ¨ØªØºÙŠØ± Ø§Ù„Ø§ØÙƒØ§Ù…Â  ØªÙƒÙˆÙ† Ø§Ù„Ø£ØÙƒØ§Ù… Ø§Ù„Ø´Ø±Ø¹ÙŠØ© Ù…Ø±Ù†Ø©ØŒ Ø¹Ø·ÙˆÙØ©ØŒ Ù„ÙŠÙ†Ø©ØŒ Ù‚Ø§Ø¨Ù„Ø© Ù„Ù„Ù…ÙˆØ§Ø¬Ù‡Ø© ØŒ Ø§Ø°Ù† ÙƒØ§Ù†Øª Ø§Ù„Ø£ØÙƒØ§Ù… Ø§Ù„Ø´Ø±Ø¹ÙŠØ© Ù‚Ø§Ø¨Ù„Ø© Ù„Ù„ØªØ¬Ø¯ÙŠØ¯ ÙˆÙ…Ù†Ø§Ø³Ø¨Ø© Ø¨ØªØ·ÙˆØ± Ø§Ù„Ø²Ù…Ø§Ù† ÙˆØ§Ù„ØªØºÙŠØ± Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ.Â Abstrak: Dinamika sosial dan hukum Islam saling memiliki keterkaitan dalam melakukan perubahan. Satu sisi perubahan sosial karena hukum Islam. Di sisi lain, perubahan hukum Islam karenaÂ  perubahan sosial. Keberadaan hukum Islam yang dibawa oleh Rasulullah Saw. dengan jelas merubah sosial masyarakat pada waktu itu dari masyarakat jahiliyyah yang berpegang kepada adat kebiasaan mereka menjadi masyarakat Islam yang berpegang kepada hukum Islam. Tetapi hukum Islam juga melakukan perubahan karena terjadinya perubahan sosial. Sesuai dengan kaidah fikih yang dibuat oleh fuqaha: â€œberubahnya fatwa dengan sebab berubahnya masa, tempat, keadaan (niat) dan adat kebiasaan.â€ Dengan melakukan perubahan hukum, maka hukum Islam itu dinamis, dan mampu beradaptasi, sehingga hukum Islam itu op tu date sesuai dengan perkembangan zaman dan perubahan sosial.